Dendritic cell vaccination combined with carboplatin/paclitaxel for metastatic endometrial cancer patients: results of a phase I/II trial - Koeneman, Bouke J.; Schreibelt, Gerty; Gorris, Mark A. J.; Hins - de Bree, Simone; Westdorp, Harm; Ottevanger, Petronella B.; de Vries, I. Jolanda M. (Frontiers in Immunology, 2024)
Background: Metastatic endometrial cancer (mEC) continues to have a poor prognosis despite the introduction of several novel therapies including immune checkpoints inhibitors. Dendritic cell (DC) vaccination is known to be a safe immunotherapeutic modality that can induce immunological and clinical responses in patients with solid tumors. Platinum-based chemotherapy is known to act synergistically with immunotherapy by selectively depleting suppressive immune cells. Therefore, we investigated the immunological efficacy of combined chemoimmunotherapy with an autologous DC vaccine and carboplatin/paclitaxel chemotherapy. Study design: This is a prospective, exploratory, single-arm phase I/II study (NCT04212377) in 7 patients with mEC. The DC vaccine consisted of blood-derived conventional and plasmacytoid dendritic cells, loaded with known mEC antigens Mucin-1 and Survivin. Chemotherapy consisted of carboplatin/paclitaxel, given weekly for 6 cycles and three-weekly for 3 cycles. The primary endpoint was immunological vaccine efficacy; secondary endpoints were safety and feasibility. Results: Production of DC vaccines was successful in five out of seven patients. These five patients started study treatment and all were able to complete the entire treatment schedule. Antigenspecific responses could be demonstrated in two of the five patients who were treated. All patients had at least one No therapy-related adverse event grade ≥3 or higher. Treatmentrelated adverse events grade ≥3 were related to chemotherapy rather than DC vaccination; neutropenia was most common. adverse events occurred due to the DC vaccination. Suppressive myeloid cells were selectively depleted in peripheral blood after chemotherapy. Conclusions: DC vaccination can be safely combined with carboplatin/paclitaxel in patients with metastatic endometrial cancer and induces antigen-specific responses in a minority of patients. Longitudinal immunological phenotyping is suggestive of a synergistic effect of the combination.